Phenomenological Study: Recreational Sports in Urban Society - Cahyo Wibowo; Alwin Praiman Hulu; Dennys Christovel Dese (Indonesian Journal of Sport Management, 2023)
People in the city have unique lifestyles and thoughts. Most people do not have time to do social activities because they are busy with various jobs. Urban people engage in sports activities for several reasons, such as reducing stress caused by their work and building social relationships. This research aims to collect data to provide an overview or confirmation of a concept regarding the phenomenon of recreational sports in the community in the city of Salatiga. Descriptive qualitative with a phenomenological approach. The subjects in this research were the people of Salatiga who played recreational sports. Data was obtained using in-depth interview methods with research subjects. The data analysis technique was carried out using Milles & Huberman; namely, data analysis carried out interactively includes four analysis components: Collection of data obtained from interviews, observations and documentation, Data reduction, Data presentation, and Interesting conclusion. The people of Salatiga City interpret recreational sports very well but still need to improve infrastructure. Recreational sports are a form of social phenomenon in the people of Salatiga city. Become reference material and consideration for maintaining and developing recreational sports for society as a sustainable social phenomenon identity.